Interactions between oxidative stress, autophagy and apoptosis in A549 cells treated with aged black carbon. (February 2019) - An, Jing; Zhou, Qian; Wu, Meiying; Wang, Lu; Zhong, Yufang; Feng, Jialiang; Shang, Yu; Chen, Yingjun
Abstract: After emitted from incomplete combustion of fossil fuels and biomass, ambient black carbon (BC) was then undergone photochemical oxidization processes in the air to form aged BC particles, also called oxidized BC (OBC). This study aimed to investigate the interactions between oxidative stress, autophagy and apoptosis induced by OBC in A549 cells and to explore associated molecular mechanisms. First, OBC could stimulate oxidative stress, autophagy and apoptosis dose-dependently, as evidenced by increased intercellular reactive oxygen species (ROS) levels, up-regulated autophagosome markers (light chain 3, LC3), and elevated apoptosis rate. Inhibitors of oxidative stress ( N -acetylcysteine, NAC), autophagy (bafilomycin A1, Baf) and apoptosis ( Z -DEVD-FMK) were used to investigate their interactions. NAC pretreatment could significantly reduce autophagy and apoptosis. Additionally, pretreatment with Baf or Z -DEVD-FMK could also significantly suppress the other two biological effects. Furthermore, OBC up regulated the expressions of DNA-dependent protein kinase catalytic subunit (DNA-PKcs), phosphorylated protein kinase B (Akt) and mammalian target of rapamycin (mTOR). The Akt inhibitor (MK-2206) significantly reduced both autophagy and apoptosis. Taken together, dual-direction regulation existed between each two of oxidative stress, autophagy, and apoptosis in A549 cells exposed to OBC. In addition, the autophagy process is modulated by the PI3K/Akt pathway regardless of mTOR activity. Graphical abstract: Highlights: Oxidized BC containing PAHs activated autophagy, apoptosis and oxidative stress in A549 cells. Dual-direction regulations existed between autophagy and apoptosis. Autophagy and apoptosis were regulated by PI3K/Akt pathway. Autophagy and apoptosis were independent of mTOR pathway